2022
DOI: 10.29408/veles.v6i2.6066
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian English Teachers’ Work Engagement and Attitudes towards the Use of Instructional Technology: A Survey Study

Abstract: The present study was conducted to investigate the level of work engagement of Indonesian high school teachers of English and its relationship with their attitudes towards the use of instructional technology (IT) during the Covid-19-driven online instruction. The study employed a survey method of distributing a Google Form questionnaire and a total of 114 teachers participated in the study. It was found that the participants generally reported a high level of work engagement in their English Language teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, the present study was conducted simultaneously with a quantitative study by Subekti and Kurniawati (2022) investigating the teacher participants' level of their work engagement as well as the relationship between their work engagement and their attitudes towards the use of IT, the focus of the present study. Both studies involved exactly the same participants.…”
Section: Participants and Ethical Considerationsmentioning
confidence: 99%
“…Additionally, the present study was conducted simultaneously with a quantitative study by Subekti and Kurniawati (2022) investigating the teacher participants' level of their work engagement as well as the relationship between their work engagement and their attitudes towards the use of IT, the focus of the present study. Both studies involved exactly the same participants.…”
Section: Participants and Ethical Considerationsmentioning
confidence: 99%
“…Employees do not quickly feel tired of all the workload they face. However, the results of a survey conducted by Subekti & Kurniawati (2022) entitled Global Workforce Study (GWS) in Indonesia found that 38% of employees who were not involved tended to leave their jobs within two years, while only around 21% of employees who had work involvement with the company %. This data will strengthen the close relationship between work engagement and the company, where employees who are involved tend to choose to stay.…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that participants enjoy the use of computers but lack competence in using them. The findings of a study by Subekti and Kurniawati (2022) reported that the teachers expressed their enthusiasm for using ICT to assist them to become more resourceful, competent, and interactive in teaching which improved the teacher-student relationship and changed the way they teach even though they make use of overly basic instructional technology. This attitude is also in line with the findings of Bingimlas (2009) and Dewi et al (2019) although teachers face numerous obstacles in their efforts to integrate ICT into teaching due to several factors that need to be considered by teachers when using technology in the classroom, such as setting objectives, examining students' needs, organizing lessons, and selecting technology tools; they have a strong desire to do so.…”
Section: Introductionmentioning
confidence: 99%